Occurrence and characterization of carbapenem‐resistant Gram‐negative bacilli: A collaborative study of antibiotic‐resistant bacteria between Indonesia and Japan. (25th September 2018) - Kuntaman, Kuntaman; Shigemura, Katsumi; Osawa, Kayo; Kitagawa, Koichi; Sato, Koharu; Yamada, Naoki; Nishimoto, Kento; Yamamichi, Fukashi; Rahardjo, Dadik; Hadi, Usman; Mertaniasih, Ni Made; Kinoshita, Shohiro; et al.
Abstract : Objectives: To explore the occurrence and characterization of carbapenemase‐producing pathogens among carbapenem‐resistant Gram‐negative bacilli isolated from hospitalized patients with urinary tract infection in Indonesia. Methods: This was a study promoted by the Japanese–Indonesian collaborative research program in the Japan Initiative for Global Research Network on Infectious Diseases. Bacterial pathogens were prospectively isolated from urine specimens of hospitalized urinary tract infection patients at Dr. Soetomo Hospital (Surabaya, Indonesia). All Gram‐negative bacteria resistant to third‐generation cephalosporin or carbapenem were included in this study. Carbapenemase genes were investigated for phenotype and genotype. Results: In total, 1082 Gram‐negative bacilli were isolated, of which 116 strains were resistant to imipenem or meropenem (carbapenem‐resistant Gram‐negative bacilli), and 22 strains were carbapenemase‐producing Gram‐negative bacilli. Carbapenemase‐producing Gram‐negative bacilli consisted of Acinetobacte r baumannii ( n  = 4), Pseudomonas aeruginosa ( n  = 4), Klebsiella pneumoniae ( n  = 5), Providencia rettgeri ( n  = 4) and five others. The carbapenemase‐producing Gram‐negative bacilli included NDM‐1 ( n  = 18, 81.8%, in Enterobacteriaceae and Acinetobacter spp.) and IMP‐7 ( n  = 4, 18.2%, all in P. aeruginosa ). Among carbapenem‐resistant Gram‐negative bacilli, all four P. aeruginosa were sensitive to colistin, and all six Acinetobacter spp. were sensitive to minocycline, colistin and tigecycline. Of those patients harboring carbapenemase‐producing Gram‐negative bacilli, 12 (54.5%) were seriously ill at the time of admission, with longer hospital stays and three deaths (13.6% mortality rate). Conclusions: Urinary tract infection‐causing carbapenem‐resistant Gram‐negative bacilli are widely disseminated in Indonesia. The NDM‐1 phenotype seems to be dominant, and it can be treated with colistin and tigecycline in most cases. Most patients harboring carbapenemase‐producing Gram‐negative bacilli are seriously ill, have a bad prognosis, with a longer hospital stay and a significant mortality rate.